Comparing Bone-Tendon Autograft With Bone-Tendon-Bone Autograft for ACL Reconstruction: A Matched-Cohort Analysis. Issue 12 (3rd December 2020) - Cruz, Christian A.; Goldberg, Daniel; Wake, Jeffrey; Sy, Joshua; Mannino, Brian J.; Min, Kyong S.; Bottoni, Craig R.
Background: Anterior cruciate ligament (ACL) reconstruction (ACLR) using bone-tendon-bone (BTB) autograft is associated with increased postoperative anterior knee pain and pain with kneeling and has the risk of intra- and postoperative patellar fracture. Additionally, graft-tunnel mismatch is problematic, often leading to inadequate osseous fixation. Given the disadvantages of BTB, an alternative is a bone-tendon autograft (BTA) procedure that has been developed at our institution. BTA is a patellar tendon autograft with the single bone plug taken from the tibia. Purpose/Hypothesis: The purpose of this study was to evaluate the short-term outcomes of BTA ACLR. We hypothesized that this procedure will provide noninferior failure rates and clinical outcomes when compared with a BTB autograft, as well as a lower incidence of anterior knee pain, pain with kneeling, and patellar fracture. Methods: A consecutive series of 52 patients treated with BTA ACLR were retrospectively identified and compared with 50 age-matched patients who underwent BTB ACLR. The primary outcome was ACL graft failure, while secondary outcomes included subjective instability, anterior knee pain, kneeling pain, and functional outcome scores (Single Assessment Numeric Evaluation, Lysholm, and International Knee Documentation Committee subjective knee form). Results: At a mean follow-up of 29.3 months after surgery, there were 2 reruptures in the BTA cohort (4.0%) and 2 in the BTB cohort (4.0%). In the BTA group, 18% of patients reported anterior knee pain versus 36% of the BTB group ( P = .04). A total of 22% of patients noted pain or pressure with kneeling in the BTA cohort, as opposed to 48% in the BTB cohort ( P = .006). There were no differences in functional scores. In the BTA group, 94.2% of patients reported that their knees subjectively felt stable, as compared with 86% in the BTB group ( P = .18). Conclusion: This study demonstrated that the BTA ACLR leads to similarly low rates of ACL graft failure requiring revision surgery, with significantly decreased anterior knee pain and kneeling pain when compared with a BTB. Additionally, the potential complications of graft-tunnel mismatch and patellar fracture are eliminated with the BTA ACLR technique.